Molecular characterization of mandarins (Citrus reticulata Blanco) using ISSR markers (2020)
In order to establish the molecular diversity of citrus production systems in Villa Sucre (Colombia), mainly “Creole mandarin”, this study analyzed C. reticulata farm samples using six ISSR molecular markers. A total of 61 polymorphisms were characterized; 42% were highly common with a mid- average polymorphic information content (PIC) of 0.42, indicating a highly polymorphic variation. Molecular relationships based on the Dice coefficient and the UPGMA algorithm showed the existing genetic relationships between the crop areas, grouping them in five separate clades and two main subgroups (MDS). This is the first molecular classification done in the area, setting the basis for mandarin crop molecular diversity and providing vital information for mandarin crop management programs.